The Effectiveness of Monetary Policy in Neutralizing Oil Price Fluctuations on the Gross Domestic Product in Iraq for the Period (1990-2019) - Younis Jassim, Raneen; Nima Bekheet, Heider (Journal of Economics and Administrative Sciences, 2022)
The research aimed to measure the reality of monetary policy and its role in neutralizing the impact of fluctuations in total domestic oil prices, through the most important monetary policy variable (money supply). An example of this is using a simple technique in the previous example, turning it into a straightforward user interface by (Judd and Kunee). After estimating the impact of the policy with the domestic gross domestic oil prices in Iraq, the effect of fluctuations in the domestic gross domestic oil prices in the simple regression model, while the morale of oil prices was not proven with a negative sign, while the morale of money supply and their impact on the increase of the domestic was proven in the multiple regression model. Statistically, interpreting this indicates that the participation of other variables to oil prices in the graph of the rate of impact absorption and a negative impact was achieved in the nature of the original variable, and through the analysis of the path and direct graph of oil prices on the GDP, the evaluation of the Iraqi economy is equal to 95% of public revenues. It amounts to 60% of Iraq’s GDP. A constant source of shocks because it is associated with cheap prices. In the light of this, the research reached a recommendation to reduce dependence on oil revenues, as it represents a permanent source of shocks due to its association with oil prices, which represents an external variable subject to market price fluctuations and the tendency to rely on other alternative sources of activating other sectors